2020
DOI: 10.5343/bms.2019.0076
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and small-scale horizontal distribution of cephalopods in the Charlie-Gibbs Fracture Zone of the Mid-Atlantic Ridge

Abstract: In summer 2009, NOAA surveyed the nekton fauna of the fracture zone on the Mid-Atlantic Ridge halfway between Iceland and the Azores as a small-scale follow-up to a previous large-scale Norwegian expedition. Midwater sampling with a Norwegian Krill Trawl resulted in 64 discrete-depth samples from 12 stations at depths from near-surface to 3000 m. Seven additional bottom samples were collected with a large trawl at depths of 2000–3500 m. The expedition collected 416 cephalopods in ca. 19 species in the vicinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…M. johnsonianus shows the most promise of using the seamounts, as there are two reported observations of this species from the Mid-Atlantic Ridge, the seamount observation from the present study, and two potential seamount observations identified only as Muusoctopus sp. from Bear Seamount (Richards & Vecchione, 2020;Shea et al, 2017;Vecchione et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…M. johnsonianus shows the most promise of using the seamounts, as there are two reported observations of this species from the Mid-Atlantic Ridge, the seamount observation from the present study, and two potential seamount observations identified only as Muusoctopus sp. from Bear Seamount (Richards & Vecchione, 2020;Shea et al, 2017;Vecchione et al, 2010).…”
Section: Discussionmentioning
confidence: 99%